Design aspects of hydrological networks - Van der Made, J. W. (The Hague / Paises Bajos, 1986)
Network design is a subject wich is of essential importance for hydrology. The system of hydrological gauging station provides the information, necessary for all other hydrological activities. In the beginning it only concerned separate gauging station. Gradually one became more interested into the coherence of the phenomena examined and the relation between the data, measured at several station.